The Controlling Role of Corporate Governance in Enhancing Firm Value through Human Resource Accounting in the Manufacturing Sector: Evidence from Nigeria - Odewusi, Oyetola O.; Adegbie, Folajimi Festus; Nwaobia, Appolos N. (Archives of Business Research, 2025)
Firm value is a critical determinant of shareholder wealth maximization and investor confidence. However, many manufacturing firms in Nigeria have not fully integrated human resource accounting (HRA) and corporate governance into their operational strategies, leading to suboptimal firm value. This study investigated the controlling role of corporate governance in enhancing firm value through human resource accounting in Nigeria’s manufacturing sector. The study employed an ex post facto research design and utilizes secondary data from 28 manufacturing firms listed on the Nigerian Exchange Group (NGX) between 2009 and 2023. Multiple regression analysis is used to evaluate the impact of HRA on firm value and the moderating effect of corporate governance. Human resource accounting has significant effect on FV of quoted firms in Nigeria (Adj.R2 = 0.237, F(14, 371) = 257.99, p <0.05), Corporate governance has significant controlling effect on FV of quoted firms in Nigeria (Adj R2 = 0.255, F(14, 369) = 329.38, p <0.05). The study concluded that Human resource accounting, corporate governance enhanced Firm Value of quoted firms in Nigeria. The study recommended that policymakers and regulators enforce global best practices in corporate governance and human resource management to enhance firm value in Nigeria’s manufacturing sector.